MOTIVASI INSTRINSIK DAN EKSTRINSIK KARYAWAN PT. CAHAYA SAKTI MULTI INTERCO CABANG PONTIANAK - B31109043, Ike Krispiyanti (Jurnal Manajemen Update, 2016)
This study was to describe the intrinsic motivation and extrinsic motivation of employees of PT. Cahaya Sakti Multi Interco Cabang Pontianak. The study was designed as a descriptive statistical study using survey. The population of this study were employees of PT. Cahaya Sakti Multi Interco Cabang Pontianak. The results showed that in general the intrinsic motivation of employees can be said to have been very high , the highest score of 187 with a predicate is as high as in the variable recognition , while the lowest score of 158 with a predicate is very high in the variable work itself , where work performance is achieved not optimal , Whereas extrinsic motivation received the title is very high , it indicates the amount of the highest scoring of 172 seen in the company's procedures , which the Company implement clear procedures on the issue of pensions. The lowest scoring of 158 with honors very high on job security variables in the execution of work ( certainty work ) which indicates that there are employees who feel there is no certainty jobs at           PT . Cahaya Sakti Multi Interco Branch Pontianak. Keywords  : Intrinsic Motivation, Extrinsic motivation PT. Cahaya Sakti Multi Interco Cabang Pontianak.